Bacterial cellulose growth on 3D acrylate-based microstructures fabricated by two-photon polymerization - Otuka, Adriano J.G.; Domeneguetti, Rafael R. [UNESP]; Moraes, Jonathas Q.R.; Balogh, Debora T.; Ribeiro, Sidney J.L. [UNESP]; Mendonça, Cleber R. (IOP Publishing, 2021)
Miniaturized environments have emerged as an excellent alternative to evaluate and understand biological mechanisms. These systems are able to simulate macroenvironments with high reproducibility, achieving many results in a short time of analysis. However, microenvironments require specific architectures that can be reached using laser micromachining techniques, such as two-photon polymerization (TPP). This technique has many advantages, allowing the production of environments without shape limitation and with special features. In this work, aided by the TPP technique, we produce different arrays of microstructures, fabricated using acrylate-based materials, in order to evaluate the growth and development of the Komagataeibacter xylinus bacteria, the micro-organism responsible for producing bacterial cellulose (BC), a natural polymer with several biological applications. BC grown in microenvironments presents similar features to those of biofilm formed in macroenvironments, maintaining their attractive properties. In addition, due to the high optical quality and mechanical resistance of the BC matrices, we use these films as flexible substrates in TPP experiments, obtaining promising results for tissue engineering studies.
Keywords: Acrylate-based materials; Bacterial cellulose growth; Two-photon polymerization